The abstract and title page - Chapnick, Jeremy Dean (AME Medical Journal, 2019)
The title page and the abstract are essential parts of any research paper or manuscript; therefore, it is vital to write them correctly and well. Why? For one, it is what researchers will use to determine if the manuscript’s content is relevant to their research for inclusion in their study. Two, online databases will use software to scan the abstract and the title page for specific keywords and ideas and use them for indexing. As a result, it is crucial to master the formatting and to understand the content which should be on a title page and inside the abstract to maximize the reach of a research paper. This chapter will delve into what is needed to write a proper title page and the abstract section, as well as providing general tips to keep in mind while drafting and writing.